ANALISIS PERBANDINGAN PRODUKTIVITAS DRILLING RIG: STUDI TEORITIS DAN OBSERVASI LAPANGAN - Hotasi Stieward, Gabriel; Muhammad Rafli Bimo Prasetyo; Sumaidi (Kohesi: Jurnal Sains dan Teknologi, 2024)
Efficiency in managing time, cost, and resources is a major challenge in modern construction projects. One crucial aspect is the use of the right heavy equipment, including drilling rigs in borepile foundation drilling work. This study focuses on the productivity analysis of the Sanny SR155-C10 drilling rig in borepile drilling work, both from a theoretical and actual perspective. The results show that the productivity of the drilling rig reaches 4.53 m3/hour, higher than the theoretical estimate of 4.07 m3/hour. The actual duration of completion of the borepile foundation drilling work is 11 working days, more efficient than the physical calculation which requires 13 working days. Factors such as weather, operator skills, and soil characteristics affect operational efficiency. These findings are expected to contribute to improving project operational efficiency through optimization of the use of drilling rigs,